(untitled) (Global Journal of Medical Research, 2020)
An analysis of the immune status in 53 patients that underwent coronary artery bypass grafting under cardiopulmonary bypass was carried out in the preoperative period and on day 1 and 7 after the surgical intervention. Significant changes in innate and adaptive immunity were revealed. In the first case, they were expressed as an inflammatory process developed throughout the postoperative period; it was confirmed with an increase in leukocytes, total and stab granulocytes, monocytes, oxidative stress of phagocytes, CD64+ and CD40+ granulocytes, endogenous intoxication with the developed significant deficiency in CD4+ monocytes, and regulatory NK cells; while immediately after the surgery, it was confirmed by IgG and IgM levels. Some changes in adaptive immunity manifested through its activation, confirmed by an increased CD4+, CD11b+, HLA-DR+, and CD4+CD25+ lymphocyte content, together with a deficiency noted in total lymphocytes and CD8+ lymphocytes.